Currency Exchange, Its Illah and Implications - Oziev, Gapur; Mohammed, Mustafa Omar; M. B. Zaidon, Muhamad Hafizi; Kamis A, Mahfuth (Journal of Islamic Finance, 2016)
Foreign exchange is among the most important transactions in any economy. It can affect positively or negatively the relative price of domestic and foreign goods, which in turn has an effect on the country’s economic growth, employment rate, inflation and balance of payments, among others. Yet, foreign exchange has remained a contentious issue among Muslim jurists and scholars. There are those who approve spot transactions but regard forward transactions as unlawful. Conversely, some scholars and jurists do not see any problem with the forward transactions if they are used for hedging purposes. In the context of the contemporary business environment, this contention requires pertinent research in need of revisiting the illah (effective cause/reason) for determining whether a given foreign exchange transaction is Shari’ah compliant. The present study has critically reviewed the major literature and fatwas issued in relation to foreign exchange. It has adopted content analysis to categorize these various views on the subject and preponderated the major ones relevant to modern business. The authors have concluded that the only possible illah to be considered for modern paper money is a thummuniyah (means of payment). The study concludes with recommendations and suggestions for future research.